2017
DOI: 10.3389/fnins.2017.00258
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MEMPRAGE, FLAIR, and R2* Segmentation to Resolve Dura and Vessels from Cortical Gray Matter

Abstract: While widely in use in automated segmentation approaches for the detection of group differences or of changes associated with continuous predictors in gray matter volume, T1-weighted images are known to represent dura and cortical vessels with signal intensities similar to those of gray matter. By considering multiple signal sources at once, multimodal segmentation approaches may be able to resolve these different tissue classes and address this potential confound. We explored here the simultaneous use of FLAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
4
29
1
Order By: Relevance
“…One important reason is the misclassification of dura and vessel sinuses as gray matter. The overestimation is mainly due to the close proximity and similarity in signal intensity of these structures to the cortex (Lindig et al, ; Viviani, Pracht, et al, ). The addition of FLAIR did resolve this misclassification for both the T1 and MP2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important reason is the misclassification of dura and vessel sinuses as gray matter. The overestimation is mainly due to the close proximity and similarity in signal intensity of these structures to the cortex (Lindig et al, ; Viviani, Pracht, et al, ). The addition of FLAIR did resolve this misclassification for both the T1 and MP2.…”
Section: Discussionmentioning
confidence: 99%
“…Improved tissue segmentation can be achieved through combining multispectral MRI contrasts in the segmentation process (Alfano et al, 1997;Ashburner & Friston, 1997;Ashburner & Friston, 2005;Fletcher, Barsotti, & Hornak, 1993;Lambert, Lutti, Helms, Frackowiak, & Ashburner, 2013;Vannier et al, 1985). Recent studies have confirmed superiority of multispectral over conventional T1-only segmentation by addressing issues such as overestimation of dura and vessels as GM and also improve cortical GM segmentation Viviani, Pracht, et al, 2017;. With the addition of T2/T2-FLAIR weighted, VBM variants (T1 + FLAIR, T1 + T2) have also shown improved lesion detection over T1-only VBM, in both lesional and non lesional MRI focal epilepsy Lindig et al, 2018).…”
mentioning
confidence: 99%
“…It is therefore possible that brain areas with inherently large vessels (or with a high density of small vessels), and hence high CBV, affect the T1-weighted intensity of nearby gray matter voxels, leading to an overestimation of thickness. In addition, other studies have investigated the potential misclassification of vessels as gray matter (Helms et al, 2006;Viviani et al, 2017). In addition, other studies have investigated the potential misclassification of vessels as gray matter (Helms et al, 2006;Viviani et al, 2017).…”
Section: Regionwise Atlas-based Venous and Arterial Density Mapsmentioning
confidence: 99%
“…Several software packages, for example, FreeSurfer (Dale, Fischl, & Sereno, 1999), FMRIB's software library (FSL; Smith et al, 2004), Statistical Parametric Mapping (SPM; Ashburner, 2009), and CBS High‐Res Brain Processing tools (Bazin et al, 2014), have been developed to automatically classify different tissue classes based on image‐specific criteria using varying segmentation algorithms, hereby putting a large emphasis on bias field removal. In addition, many of these packages allow incorporation of complementary MRI data, such as normalT2(*)‐ or proton density (PD)‐weighted images, to improve the accuracy of the (i.e., multimodal) segmentation algorithm by identifying nonbrain tissue, for example, dura mater and blood vessels (Helms, Kallenberg, & Dechent, 2006; Lambert, Lutti, Helms, Frackowiak, & Ashburner, 2013; Viviani et al, 2017). …”
Section: Introductionmentioning
confidence: 99%